MENTAL HEALTH AND ITS CORRELATION WITH THE ACADEMIC ACHIEVEMENT OF STUDENT OF FACULTY OF ECONOMY IN UNIVERSITAS ADVENT INDONESIA BANDUNG - Romulo Sinabutar (Jurnal Ekonomis, 2020)
The research design was a descriptive correlation with cross sectional study. Descriptive correlational study design is to understand the correlation between independent variables (mental health) with the academic achievement of student of economic in Universitas Advent Indoneia Bandung as the dependent variable. The approach used in this study is cross sectional approach, means a research subject has only been observed once and measurements were performed simultaneously at the same time The sample are students which utilize by questionnaire, non-structure questions, and an accidental sampling method. Analysis and interpretation of data are using Zung Self-Assessment of Depression Scale (ZSDS), and Depression Anxiety Stress Scales (DASS 42), and multi linear regression analysis. The three variables under mental health (depression, anxiety and stress) have an inverse correlation meaning that the lower the level of depression, anxiety and stress then the relationship indicates academic achievement is higher.